Using Seawater for Weed Management in Turfgrass - Uddin, Md. Kamal (2010)
Long term use of herbicide can pose serious threat to environment. Alternative strategies to chemical herbicide in weed control have received increasing attention now a days. Salty water could be used to control weed in salt tolerant turfgrass areas. A series of experiments were conducted to examine the response of turfgrass species, common local weed species and soil microbial communities to salinity stress both singly and in combination with reduced rates of recommended herbicides. The plant species selected for evaluation in these studies were based on a detailed preliminary survey conducted in local turfgrass areas. Four salinity levels (0, 24, 48 and 72 dSm-1) were imposed on 16 turfgrass entries in glasshouse experiments to identify potential salt tolerant turf species. Tolerance ranking was based on 50% reduction of shoot and root dry weights, leaf firing and turf quality.Predicted salinity levels for 50% shoot and root growth reductions were, 17.0 – 39.8 and 18.8 – 49.4 dS m-1, respectively. Paspalum vaginatum proved to be superior in salt tolerance, and was closely followed by Zoysia japonica and Zoysia matrella. In the field survey of four different turfgrass areas, 79 weed species belonging to 16 families were recorded. Maximum numbers of weed species were found on residential lawns, while least numbers were recorded on golf course putting greens; athletic fields and sod farms ranked intermediate. Cyperus aromaticus yielded the highest relative abundance value in golf course putting greens (71.5), followed by athletic fields (45.5) and residential lawns (21.7). Fimbristylis dichotoma and Cyperus compressus yielded the highest relative abundance values on residential lawns (35.0) and sod farms (30.4), respectively. In studies evaluating the use of saline solutions for weed control, the same four salinity levels (0, 24, 48 and 72 dS m-1) were applied to all 79 weed species, along with P. vaginatum (as a control). The results on injury ratings for salt tolerant weeds were categorized as highly susceptible, moderately susceptible and extremely tolerant. The results showed that 44 weed species were very susceptible and found to be effectively controlled (100%) at salinities of 24 and 48 dS m-1, while 30 species were found to be effectively controlled with the 72 dS m-1 salinity treatment. The five most serious weeds viz. Eragrostis atrovirens, Sporobolus diander, Cyperus aromaticus, Cyperus rotundus and Emilia sonchifolia were found to be extremely tolerant, and were not controlled even at the highest salinity level of 72 dS m-1. In the physiological study, three most tolerant and three least tolerant turf species were subjected to seven salinity levels (0, 8, 16, 24, 32, 40 and 48 dS m-1) treatments and were assessed for leaf proline, chlorophyll and relative water contents. Leaf firing, plant biomass, and concentrations of Na, K, Ca, and Mg in shoots and roots were also determined. Root structure injury was observed under a scanning electron microscope (SEM). In general, trends of proline concentrations were found to increase with increasing salinity levels. However, there was an extremely higher rate of increase in salt tolerant species than in sensitive ones. Zoysia japonica was the least Na accumulating at all salinity levels followed by P. vaginatum and Z. matrella, while D.didactyla was the highest Na accumulating species followed by Cynodon dactylon ‘satiri’ and Cynodon dactylon ‘tifdrawf’. Paspalum vaginatum always had greater K contents at all salinity levels followed by Z. japonica and Z. matrella. On the other hand, the lowest K contents were recorded in C.dactylon ‘tifdwarf’ followed by C.dactylon ‘satiri’ and D. didactyla. Salinity caused root cortex cells to collapse, in C.dactylon ‘tifdwarf’, C. dactylon ‘satiri’ and D. didactyla at highest salinity level (48 dS m-1), but not in P. vaginatum , Z. japonica and Z. matrella. Soil microbes were more or less affected by application of either herbicides, sea water or in combination. However,salt water treatment in combination with reduced herbicide are more eco-friendly than other options. Sensitivity to seawater plus reduced rates of herbicide was evaluated for E. atrovirens,S. diander, C. aromaticus, C. rotundus and E. sonchifolia as well as for turfgrasses viz. P. vaginatum, C. dactylon ‘satiri’, and Z. japonica. The weed species S. diander, C.aromaticus, C. rotundus and E. sonchifolia except E. atrovirens were fully controlled when treated with ¾ recommended trifloxysulfuron–sodium with sea water, ¾ recommended trifloxysulfuron–sodium with ¾ sea water, ½ recommended trifloxysulfuron–sodium with sea water, ¾ recommended quinclorac with sea water and ¾ recommended quinclorac with ¾ sea water. Eragrostis atrovirens showed maximum 48% injury when treated with ¾ recommended trifloxysulfuron–sodium and sea water. Among the tested turfgrasses, P. vaginatum showed only 8% injury to sea water in combination with ¾ recommended quinclorac, indicating greater salt tolerance. Zoysia japonica also showed no more than 14% injury when treated with sea water in combination with ¾ recommended trifloxysulfuron–sodium or quinclorac. Cynodon dactylon ‘satiri’ had up to 21% salt injury with ¾ sea water in combination with ¾ recommended trifloxysulfuron –sodium.